Structure–Activity Relationship Studies in a Series of 2-Aryloxy-N-(pyrimidin-5-yl)acetamide Inhibitors of SLACK Potassium Channels - Nigam M. Mishra; Brittany D. Spitznagel; Yu Du; Yasmeen K. Mohamed; Ying Qin; C. David Weaver; Kyle A. Emmitte (Molecules)
Epilepsy of infancy with migrating focal seizures (EIMFS) is a rare, serious, and pharmacoresistant epileptic disorder often linked to gain-of-function mutations in the KCNT1 gene. KCNT1 encodes the sodium-activated potassium channel known as SLACK, making small molecule inhibitors of SLACK channels a compelling approach to the treatment of EIMFS and other epilepsies associated with KCNT1 mutations. In this manuscript, we describe a hit optimization effort executed within a series of 2-aryloxy-N-(pyrimidin-5-yl)acetamides that were identified via a high-throughput screen. We systematically prepared analogs in four distinct regions of the scaffold and evaluated their functional activity in a whole-cell, automated patch clamp (APC) assay to establish structure-activity relationships for wild-type (WT) SLACK inhibition. Two selected analogs were also profiled for selectivity versus other members of the Slo family of potassium channels, of which SLACK is a member, and versus a panel of structurally diverse ion channels. The same two analogs were evaluated for activity versus the WT mouse channel as well as two clinically relevant mutant human channels.